Image data compression using DCT (Discrete Cosine Transform) and interpolation And allied topics in digital image processing applied to satellite imaging - Sathyanarayana, Pabbisetti; Md Sahar, Aftanasar (Universiti Sains Malaysia, 2007)
Digital image processing plays an important role in modern scientific endeavors. It has specific uses in satellite imaging, remote sensing, telemetry and medical imaging. Image processing requires huge memory space to store the data, and to process the data in real time high speed computers are required.